Analisis Pertumbuhan Ekonomi Dan KetimpanganPendapatan Di Wilayah Subosukowonosraten Periode 1990 - 2014 - Fitrianasari, Marleni Rias; , Daryono Soebagyo, M.Ec (2016)
This study entitled "Analysis of Economic Growth and Income Inequality In Area SUBOSUKOWONOSRATEN Period 1990-2014". The purpose is to reveal the pattern and structure of economic growth in each region in the area Subosukowonosraten based economic growth and GDP per capita as well as to analyze the level of income inequality in the region SUBBOSUKOWONOSRATEN (Surakarta, Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen, Klaten). The data used in this research is secondary data. The analytical methods used are tipology Klassen and williamson index. The results showed using Klassen tipology analysis can be concluded that in Surakarta is in the first quadrant (local fast forward and fast-growing) and the second quadrant (fast growing area). Boyolali entered in the third quadrant (forward but depressed areas) and fourth (relatively underdeveloped regions). Sukoharjo entry in the first quadrant (local fast forward and fast-growing), the second quadrant (fast growing area), the third quadrant (forward but depressed areas) and the fourth quadrant (relatively underdeveloped regions). Karanganyar entry in the first quadrant (local fast forward and fast-growing), the second quadrant (fast growing area), the third quadrant (forward but depressed areas), and the fourth quadrant (relatively underdeveloped regions). In Wonogiri and Klaten district located in the third quadrant (forward but depressed areas) and the fourth quadrant (relatively underdeveloped regions). While in Sragen entry in the first quadrant (local fast forward and fast-growing), the third quadrant (forward but depressed areas) and the fourth quadrant (relatively underdeveloped regions). Based on the analysis of Williamson index, shows that the average inequality that occurred in the period 1990-2014 amounted to 0.322 SUBOSUKOWONOSRATEN. SUBOSUKOWONOSRATEN income inequality in the region is still relatively low, but non-significant increase in observation